A Vector Bond Graph Method of Dynamics Modeling for Planar Multi-body Systems with Grooved Sheave - Wang Zhongshuang; Zhao Yanwei; Xu Changshun (Jixie chuandong)
In order to increase the reliability and efficiency of the dynamics modeling and analysis for complex planar multi-body systems containing grooved sheave,the corresponding vector bond graph procedure is proposed. From the kinematic constraint condition,the vector bond graph model of point-linear follower is built,which is suitable for inner and external grooved sheave. Based on this,the procedure to mode planar multi-body systems with grooved sheave by vector bond graph is made. For the algebraic difficulties brought by differential causality and nonlinear junction structure in dynamics modeling of the planar multi-body systems,the effective decoupling method is proposed. By using the corresponding algorithm,the computer automatic modeling and dynamics analysis of the planar multi-body system containing grooved sheave on a computer is realized,its validity is illustrated.